Search for CP violation in Bs0→μ+Ds-X decays in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2010)
We have performed a search for CP violation in a sample of Bs0→μ+Ds-X decays corresponding to 5fb-1 of proton-antiproton collisions collected by the D0 detector in Run II at the Fermilab Tevatron Collider. New physics in Bs0 mixing could contribute a significant CP violating weak phase, which would be observed as a difference in the decay-time distribution for Bs0→B̄s0 oscillated states versus that for B̄s0→Bs0. A fit to the decay-time distributions of the Bs0/B̄s0 candidates yields the flavor-specific asymmetry afss=[-1.7±9.1(stat)-1.5+1.4(syst)]×10-3, which excludes CP violation due to new physics within the experimental sensitivity. © 2010 The American Physical Society.